The Belarusian-Polish borderland in the works of Maria Rodziewiczówna of 1920–30s: the specifics of the artistic display - Khmialnitski, Mikalai M. (Journal of the Belarusian State University. Philology, 2019)
The article is devoted to the study of the problems of the Belarusian-Polish borderland in the works of Maria Rodziewiczówna of 1920–30s in light of the historical events and socio-cultural context. It has been revealed, at what levels the Belarusian realities, images and motives are presented and function in the work of Polish writer. Particular attention is drawn to the artistic strategies of implementation of life and traditions of the inhabitants of Belarusian Polesie in the works of M. Rodziewiczówna. The author was able to recreate the life on the Belarusian-Polish borderland during dramatic periods (World War I, occupation, Soviet-Polish War) in the most realistic manner. The subject of the research in the article are the specificity of the narration, landscape paintings, figurative-style techniques, psychologism, autobiographical discourse, Belarusian heroes and realities in the works of M. Rodziewiczówna of the 1920–30s.